Safe Injection in the Context of IPC – Changing Landscape in Nigeria - SOWANDE, Abimbola Oludotun; Jibowu, Olufunke Lami; Amaefule, Kelechi Enweruzo; Pearson, Jennifer; Iyortim, Isa (International Journal of Infection Control, 2014)
Background: Unsafe injection leads to an increased disease burden and deaths from transmission of infection. Cost effective injection safety (IS) interventions encourage best practices especially in low resource countries where the burden is highest. Infection prevention and control (IPC) among health workers, waste handlers, and communities has been documented to decrease the burden over time. Intervention: AIDSTAR-One, a PEPFAR funded project through USAID, adopted the World Health Organization technical approach that promotes sustainability by working with and through government structures and relevant stakeholders for policy development and implementation. Training and capacity building, provision of seed stock of IS commodities, behavioral communication and changes to effect new skills, appropriate healthcare waste management (HCWM), and supportive monitoring and evaluation guide interventions for effective impact. Investors are encouraged to manufacture IS commodities in-country to support the intervention. Community interventions, through existing credible structures, aim to reduce unnecessary injections, and HCWM interventions focus on a minimum package of best practice standards at the health facility level and through community involvement. Challenges: The Nigerian health system is generally weak, attrition of trained personnel due to brain drain is a continuing challenge, and health worker behavioral change is gradual. Conclusion: Injection safety interventions in countries with low resources, such as Nigeria, are generally making steady progress over time as stakeholders appreciate its importance as a key IPC measure to ensure the safety of the health workforce, patients, and communities.